EFEKTIVITAS BUS TRANS PADANG SEBAGAI MODA TRANSPORTASI PUBLIK DI KOTA PADANG - Rezki Tri Ananda; Sri Mariya (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This study aims to determine the effectiveness of the Trans Padang Bus as a mode of public transportation in the city of Padang, which is seen from 5 aspects namely accessibility, capacity, timeliness, safety and comfort, as well as tariff or price. The data used consists of primary and secondary data. Primary data obtained through observation and structured interviews of 60 random passengers. While secondary data were obtained from literature studies and related institutions. The method used is a simple scoring technique with effectiveness class that is Effective, Quite effective, and Not effective. The results of this study found that the Trans Padang Bus as a mode of public transportation in the city of Padang is